Incursion of Novel Eurasian Low Pathogenicity Avian Influenza H5 Virus, Australia, 2023 - Michelle Wille; Victoria Grillo; Silvia Ban de Gouvea Pedroso; Natasha D. Brohier; Ivano Broz; Charlotte Burgoyne; Allison Crawley; Kelly Davies; Mark Ford; Joanne Grimsey; Nina Y.H. Kung; Jasmina M. Luczo; et al. (Emerging Infectious Diseases)
Australia is a sink for low pathogenicity avian influenza viruses, with isolated circulation occurring on the continent. We report the incursion of a Eurasian low pathogenicity avian influenza H5 virus into Australia. This report benefits surveillance and diagnostic work because of the risk and current absence of highly pathogenic avian influenza A(H5N1).